Composite material and preparation method thereof, light-emitting device and display device

By using composite materials of inorganic particles, siloxane compounds and fluorine-containing compounds, the problems of surface defects and uneven sizes of inorganic particles are solved, and the stability and performance of the light emitting device are improved.

CN119730679APending Publication Date: 2025-03-28TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311281958.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the preparation process, existing inorganic particles have many surface defects and uneven sizes, resulting in low transmission efficiency of carrier functional layers, which in turn affects the performance and stability of the light emitting device.

Method used

A composite material is used, which includes inorganic particles, siloxane compounds and fluorine-containing compounds. The inorganic particles and fluorine-containing compounds are connected through siloxane compounds to form an inner and outer bilayer ligand, thereby enhancing the binding force and stability of the inorganic particles.

Benefits of technology

It improves the stability of inorganic particles and photoelectric conversion efficiency, extends the service life of the light-emitting device, and improves the luminous performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730679A_ABST
    Figure CN119730679A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a light-emitting device and a display device, and relates to the technical field of display. The composite material comprises inorganic particles, a siloxane compound and a fluorine-containing compound, wherein the siloxane compound is connected with the inorganic particles and the fluorine-containing compound, and the fluorine-containing compound contains fluorinated chain alkyl. The composite material provided by the invention is good in stability and high in solubility and degree of freedom, and beneficial properties of the composite material can be brought into play.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a composite material, a method for preparing the composite material, a light-emitting device including the composite material, and a display device including the light-emitting device. Background Art

[0002] The widely used light-emitting devices at present are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). OLED has become the mainstream technology in the field of display technology due to its excellent display performance such as self-luminescence, simple structure, ultra-light and thin, fast response speed, wide viewing angle, low power consumption, and flexible display. QLED has the advantages of saturated color of emitted light and adjustable wavelength, and high quantum yield of photoluminescence and electroluminescence. It has become a strong competitor of OLED in recent years. The structure of traditional OLED and QLED devices generally includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting diode and the electrons generated by the cathode move, are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules to finally produce visible light.

[0003] Inorganic semiconductor particles have the advantages of good stability, high transparency, safety and non-toxicity, and are often used as carrier functional materials in light-emitting devices. However, the inorganic particles currently prepared by solution method or sol-gel method have many surface defects, are large in size and uneven, and are prone to form carrier capture centers and exciton recombination centers, which reduce the transmission efficiency of the carrier functional layer and cause the performance of the light-emitting device to decay rapidly.

[0004] In order to solve the above problems, the current solution is mainly to modify the surface of inorganic particles by physical or chemical methods to improve their stability and photoelectric conversion efficiency. However, these methods have certain limitations, and the surface of the modified inorganic particles is still not stable enough. Summary of the invention

[0005] In view of this, the present application provides a composite material and a preparation method thereof, a light-emitting device, and a display device, aiming to improve the problem of poor stability of existing inorganic particles.

[0006] The embodiment of the present application is implemented as follows: a composite material includes inorganic particles, a siloxane compound and a fluorine-containing compound; wherein the siloxane compound connects the inorganic particles and the fluorine-containing compound, and the fluorine-containing compound contains a fluorinated chain hydrocarbon group.

[0007] Optionally, in some embodiments of the present application, in the composite material, the molar ratio of the inorganic particles, the siloxane compound and the fluorine-containing compound is 1:(0.005-0.45):(0.005-0.4).

[0008] Optionally, in some embodiments of the present application, the inorganic particles and the siloxane compound are connected via a connecting group; and / or

[0009] The siloxane compound comprises alkoxysiloxane; and / or

[0010] The fluorinated hydrocarbon group is a straight-chain or branched fluorinated alkyl group having 1 to 10 carbon atoms in the main chain, a straight-chain or branched fluorinated alkenyl group having 1 to 10 carbon atoms in the main chain, or a combination of these groups.

[0011] Optionally, in some embodiments of the present application, the material of the inorganic particles includes one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials, and IB-IIIA-VIA semiconductor materials, and the material of the first undoped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following, the metal oxide in the first doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 、Al 2 O 3 The doping element in the first doped metal oxide particles includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS, the IIIA-VA semiconductor material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; the second doped metal oxide particles, the second undoped metal oxide particles, one or more of metal sulfides, metal selenides, and metal nitrides, the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles each independently include MoO 3 , WO 3 、NiO、CrO 3, CuO, Cu 2 O.V 2 O 5 The doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, and V, and the metal sulfide includes CuS, MoS 3 , WS 3 One or more of the metal selenides, wherein the metal selenides include MoSe 3 ,WSe 3 One or more of the following, wherein the metal nitride comprises P-type gallium nitride; and / or

[0012] The average particle size of the inorganic particles is 5nm to 10nm; and / or

[0013] The linking group includes one or more of -COO-, -O-, -NH-CO-, -NH-, -CO-; and / or

[0014] The alkoxysiloxane includes one or more of (3-mercaptopropyl)trimethoxysilane, 3-aminopropyltrimethoxysilane, (3-propylamino)propyltriethoxysilane, and 3-methoxypropyltrimethoxysilane; and / or

[0015] The fluorine-containing compound includes one or more of perfluoroisopropionyl chloride, perfluoro-n-butyryl chloride, perfluoroacryloyl chloride and perfluorohexanoyl chloride.

[0016] Optionally, in some embodiments of the present application, the silicon-oxygen bond of the siloxane compound is connected to the connecting group; and / or

[0017] The siloxane compound contains -NH-, -OCH 2 - one or more of the fluorine-containing compound containing -CO-, the siloxane compound containing -NH- and / or -OCH 2 - is connected to the -CO- of the fluorine-containing compound.

[0018] Accordingly, an embodiment of the present application further provides a method for preparing a composite material, comprising:

[0019] Providing an inorganic particle dispersion, wherein the inorganic particle dispersion comprises inorganic particles and a first solvent;

[0020] Providing a siloxane compound, and mixing the siloxane compound with the inorganic particle dispersion to obtain an intermediate solution, wherein the intermediate solution includes an intermediate and a fourth solvent;

[0021] A fluorine-containing compound is provided, wherein the fluorine-containing compound contains a fluorinated chain hydrocarbon group, and the fluorine-containing compound is mixed with the intermediate solution to obtain a composite material.

[0022] Optionally, in some embodiments of the present application, the inorganic particles and the siloxane compound are connected via a linking group, and the linking group includes one or more of -COO-, -O-, -NH-CO-, -NH-, and -CO-; and / or

[0023] The siloxane compound includes one or more of (3-mercaptopropyl)trimethoxysilane, 3-aminopropyltrimethoxysilane, (3-propylamino)propyltriethoxysilane, and 3-methoxypropyltrimethoxysilane; and / or

[0024] The fluorine-containing compound includes one or more of perfluoroisopropionyl chloride, perfluoro-n-butyryl chloride, perfluoroacryloyl chloride, and perfluorohexanoyl chloride; and / or

[0025] The first solvent and the fourth solvent independently include one or more of ethanol, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, ethyl acetate, pyrrole, butyric acid, and cresol.

[0026] Optionally, in some embodiments of the present application, the molar ratio of the inorganic particles, the siloxane compound and the fluorine-containing compound is 1: (0.01-0.5): (0.01-0.5); and / or

[0027] In the inorganic particle dispersion, the molar concentration of the inorganic particles is 0.3 mmol / L to 0.8 mmol / L; and / or

[0028] In the intermediate solution, the molar concentration of the intermediate is 0.5 mmol / L to 1 mmol / L.

[0029] Optionally, in some embodiments of the present application, the intermediate includes the inorganic particles and a siloxane compound connected to the inorganic particles; and / or

[0030] The composite material includes inorganic particles, a siloxane compound connected to the inorganic particles, and a fluorine-containing compound connected to a surface side of the siloxane compound away from the inorganic particles.

[0031] Correspondingly, an embodiment of the present application further provides a light-emitting device, comprising: a first electrode, a first carrier functional layer, a light-emitting layer, and a second electrode stacked in sequence, wherein the material of the first carrier functional layer comprises the above-mentioned composite material.

[0032] Optionally, in some embodiments of the present application, the light-emitting device also includes a second carrier functional layer, which is arranged between the light-emitting layer and the second electrode; the first carrier functional layer is an electron functional layer, and the second carrier functional layer is a hole functional layer, or the first carrier functional layer is a hole functional layer, and the second carrier functional layer is an electron functional layer.

[0033] Optionally, in some embodiments of the present application, the materials of the first electrode and the second electrode respectively include one or more of a metal, a carbon material and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO 2 / Ag / TiO 2 and TiO 2 / Al / TiO 2 One or more of; and / or

[0034] The materials of the light-emitting layer include 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium], diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonds, HLCT materials, Exciplex luminescent materials. Materials, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, Hg STe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSe Te, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP , GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAl NSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, CuInS 2 、CuInSe 2 、AgInS 2, CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / Zn S, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, InP / ZnSe / ZnS, AMX 3 and BMX 3 One or more of the following, where A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of; B is an organic amine cation selected from CH 3 (CH 2 ) n-2 NH 3 + or [NH 3 (CH 2 ) n NH 3 ] 2+ , where n ≥ 2; and / or

[0035] When the first carrier functional layer is an electronic functional layer, the inorganic particles in the first carrier functional layer include one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials, and the material of the first undoped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following, the metal oxide in the first doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O5 、Al 2 O 3 The doping element in the first doped metal oxide particles includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor material includes one or more of InP and GaP. The IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS. When the first carrier functional layer is a hole functional layer, the inorganic particles in the first carrier functional layer include one or more of second doped metal oxide particles, second non-doped metal oxide particles, metal sulfides, metal selenides, and metal nitrides. The metal oxide in the second doped metal oxide particles and the metal oxide in the second non-doped metal oxide particles each independently include MoO 3 , WO 3 、NiO、CrO 3 , CuO, Cu 2 O.V 2 O 5 The doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, and V, and the metal sulfide includes CuS, MoS 3 , WS 3 One or more of the metal selenides, wherein the metal selenides include MoSe 3 ,WSe 3 One or more of the following, wherein the metal nitride comprises P-type gallium nitride; and / or

[0036] When the second carrier functional layer is an electronic functional layer, the material of the second carrier functional layer includes one or more of the above-mentioned composite material, first doped metal oxide particles, first non-doped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials, and the material of the first non-doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following, the metal oxide in the first doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5、Al 2 O 3 The doping element in the first doped metal oxide particles includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS, the IIIA-VA semiconductor material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; or, when the second carrier functional layer is a hole functional layer The materials of the second carrier functional layer include the above-mentioned composite material, 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-triphenylamine, (N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)triphenylamine] yl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS doped with s-MoO 3The invention relates to one or more of derivatives of poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfide, metal selenide and metal nitride, wherein the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles each independently include MoO 3 , WO 3 、NiO、CrO 3 , CuO, Cu 2 O.V 2 O 5 The doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, and V, and the metal sulfide includes CuS, MoS 3 , WS 3 One or more of the metal selenides, wherein the metal selenides include MoSe 3 ,WSe 3 One or more of the above, wherein the metal nitride comprises P-type gallium nitride.

[0037] Optionally, in some embodiments of the present application, the thickness of the first electrode is 30 nm to 80 nm; and / or

[0038] The thickness of the first carrier functional layer is 20nm to 60nm; and / or

[0039] The thickness of the light-emitting layer is 20nm to 60nm; and / or

[0040] The thickness of the second carrier functional layer is 20nm to 60nm; and / or

[0041] The thickness of the second electrode is 30 nm to 80 nm.

[0042] Correspondingly, an embodiment of the present application further provides a display device, which includes the above-mentioned light-emitting device.

[0043] The composite material provided by the present application includes inorganic particles, siloxane compounds connected to the surface of the inorganic particles, and fluorine-containing compounds connected to the side of the siloxane compound away from the inorganic particles. The fluorine-containing compound contains fluorinated chain hydrocarbon groups. The composite material provided by the present application has good stability, high solubility and degree of freedom, which is conducive to the realization of the beneficial properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0045] Figure 1 is a schematic diagram of the structure of the composite material provided in the embodiment of the present application;

[0046] Figure 2 is a flow chart of a method for preparing a composite material provided in an embodiment of the present application;

[0047] Figure 3 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;

[0048] Figure 4 It is a schematic diagram of the structure of another light-emitting device provided in an embodiment of the present application.

[0049] Reference numerals:

[0050] Inorganic particles 10; siloxane compound 20; fluorine-containing compound 30; bonding group 40;

[0051] The first electrode 100 ; the first carrier functional layer 200 ; the electron injection layer 201 ; the electron transport layer 202 ; the light emitting layer 300 ; the second carrier functional layer 400 ; the hole transport layer 401 ; the hole injection layer 402 ; and the second electrode 500 . DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0053] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0054] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0055] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0056] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0057] The technical solution of this application is as follows:

[0058] See also Figure 1 An embodiment of the present application provides a composite material, comprising: inorganic particles 10, siloxane compounds 20 and fluorine-containing compounds 30; wherein the siloxane compounds 20 connect the inorganic particles 10 and the fluorine-containing compounds 30, and the fluorine-containing compounds 30 contain fluorinated chain hydrocarbon groups.

[0059] It can be understood that the siloxane compound 20 has a structure in which two atoms or groups are lost after reacting with the inorganic particles 10 and the fluorine-containing compound 30. The fluorine-containing compound 30 has a structure in which one atom or group is lost after reacting with the siloxane compound 20.

[0060] The composite material described in the present application includes an inorganic particle 10, a siloxane compound 20 connected to the surface of the inorganic particle 10, and a fluorine-containing compound 30 connected to the side of the siloxane compound 20 away from the inorganic particle 10. The fluorine-containing compound 30 contains a fluorinated chain hydrocarbon group. The siloxane compound 20 and the fluorinated chain hydrocarbon group respectively form an inner and outer double-layer ligand of the inorganic particle 10. The inner layer of the siloxane compound 20 has a strong binding ability with the inorganic particle 10, which can improve its binding force and stability with the inorganic particle 10. The outer layer of the fluorine-containing compound 30 can reduce the chemical reaction activity on the surface of the inorganic particle 10, inhibit the redox reaction, and improve the stability of the inorganic particle 10. The fluorinated chain hydrocarbon group has a small steric hindrance, which can improve the yield of binding with the siloxane compound 20, which is beneficial to improving the solubility and freedom of the composite material and promoting the performance of the beneficial properties of the composite material.

[0061] Furthermore, when the composite material is applied to the carrier functional layer in a light-emitting device, the carrier mobility can be improved, and by inhibiting the redox reaction between the carrier and the electrode interface, the efficiency and stability of the light-emitting device can be improved, thereby improving the luminescence performance and service life of the light-emitting device.

[0062] In some embodiments, the inorganic particles 10 and the siloxane compound 20 are connected via a linking group. Further, the linking group includes one or more of -COO-, -O-, -NH-CO-, -NH-, and -CO-. It is understood that the linking group is introduced into the inorganic particles 10 during the preparation process. For example, when zinc acetate is used to prepare the zinc oxide inorganic particles 10, hydroxyl and carboxyl groups are introduced. Therefore, the linking group can be carried by the inorganic particles 10 themselves, without the need to add a ligand containing a linking group separately for modification.

[0063] In some embodiments, the material of the inorganic particles 10 includes one or more of a first doped metal oxide particle, a first undoped metal oxide particle, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material, and an IB-IIIA-VIA semiconductor material, wherein the material of the first undoped metal oxide particle includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following, the metal oxide in the first doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 、Al 2 O 3The doping element in the first doped metal oxide particles includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS, the IIIA-VA semiconductor material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; the second doped metal oxide particles, the second undoped metal oxide particles, one or more of metal sulfides, metal selenides, and metal nitrides, the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles each independently include MoO 3 , WO 3 、NiO、CrO 3 , CuO, Cu 2 O.V 2 O 5 The doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, and V, and the metal sulfide includes CuS, MoS 3 , WS 3 One or more of the metal selenides, wherein the metal selenides include MoSe 3 ,WSe 3 One or more of the above, wherein the metal nitride comprises P-type gallium nitride.

[0064] In some embodiments, the average particle size of the inorganic particles 10 is 5 nm to 10 nm, for example, 5.5 nm to 9.5 nm, 6 nm to 9 nm, 6.5 nm to 8.5 nm, 7 nm to 8 nm, etc.

[0065] In some embodiments, the silicone compound 20 includes alkoxysiloxane.

[0066] Furthermore, the alkoxysiloxane includes one or more of (3-mercaptopropyl)trimethoxysilane (MPTS), 3-aminopropyltrimethoxysilane (APTES), (3-propylamino)propyltriethoxysilane (APES), and 3-methoxypropyltrimethoxysilane (KBM-403).

[0067] It can be understood that the siloxane compound 20 contains a silicon-oxygen bond, ie, a Si—O bond.

[0068] In some embodiments, the siloxane compound 20 has a silicon-oxygen bond connected to the linking group. It is understood that the linking group contains -H, the silicon-oxygen bond contains -O, and -H reacts with -O to form H2 O, so that the siloxane compound 20 is connected to the inorganic particles 10.

[0069] In some embodiments, the fluorinated hydrocarbon group can be a straight chain or branched chain fluorinated alkyl group having 1 to 10 main chain carbon atoms, a straight chain or branched chain fluorinated alkenyl group having 1 to 10 main chain carbon atoms, or a combination of these groups.

[0070] In other embodiments, the fluorinated hydrocarbon group may be a straight-chain or branched fluorinated alkyl group with 1 to 5 carbon atoms in the main chain, a straight-chain or branched fluorinated alkenyl group with 1 to 5 carbon atoms, or a combination of these groups.

[0071] In other embodiments, the fluorinated hydrocarbon group may be a straight-chain or branched fluorinated alkyl group with 2 to 4 carbon atoms in the main chain, a straight-chain or branched fluorinated alkenyl group with 2 to 4 carbon atoms, or a combination of these groups.

[0072] In some embodiments, the fluorine-containing compound 30 includes one or more of perfluoroisopropionyl chloride (FPrC), perfluorobutyryl chloride (FBuC), perfluoroacryloyl chloride (FAC3), and perfluorohexanoyl chloride (FHC).

[0073] In some embodiments, the siloxane contains -NH-, -OCH 2 -One or more of the following.

[0074] In some embodiments, the fluorine-containing compound 30 contains -CO-.

[0075] In some embodiments, the -NH- and / or -OCH 2 - is connected to the -CO- of the fluorine-containing compound 30. Figure 1 As shown, the -NH- and / or -OCH 2 - is connected with the -CO- to form a bonding group 40, thereby realizing the connection between the siloxane and the fluorine-containing compound.

[0076] In some embodiments, in the composite material, the molar ratio of the inorganic particles 10, the siloxane compound 20, and the fluorine-containing compound 30 is 1: (0.005-0.45): (0.005-0.4), for example, it can be 1: (0.008-0.42): (0.008-0.42), 1: (0.01-0.4): (0.01-0.4), 1: (0.05-0.35): (0.05-0.35), 1: (0.1-0.3): (0.1-0.3), 1: (0.2-0.25): (0.2-0.25), etc. Within the molar range, the composite material has high stability.

[0077] See also Figure 2 The present application also provides a method for preparing a composite material, comprising:

[0078] S11: providing a dispersion of inorganic particles 10, wherein the dispersion of inorganic particles 10 comprises inorganic particles 10 and a first solvent;

[0079] S12: providing a siloxane compound 20, and mixing the siloxane compound 20 with the inorganic particle 10 dispersion to obtain an intermediate solution, wherein the intermediate solution includes an intermediate and a second solvent;

[0080] S13: providing a fluorine-containing compound 30, wherein the fluorine-containing compound 30 contains a fluorinated chain hydrocarbon group, and mixing the fluorine-containing compound 30 with the intermediate solution to obtain a composite material.

[0081] In the step S11:

[0082] In some embodiments, in the dispersion of the inorganic particles 10, the molar concentration of the inorganic particles 10 is 0.3 mmol / L to 0.8 mmol / L, for example, 0.35 mmol / L to 0.75 mmol / L, 0.4 mmol / L to 0.7 mmol / L, 0.45 mmol / L to 0.65 mmol / L, 0.5 mmol / L to 0.6 mmol / L, 0.52 mmol / L to 0.55 mmol / L, etc. Within the molar concentration range, it is beneficial for the inorganic particles 10 to be uniformly dispersed.

[0083] In some embodiments, the first solvent includes one or more of ethanol, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide (DMSO), acetone, acetophenone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethyl acetate, pyrrole, butyric acid, and cresol.

[0084] In some embodiments, the method for preparing the inorganic particles 10 includes:

[0085] Providing a metal salt and a third solvent to obtain a metal salt solution;

[0086] providing a base and a fourth solvent to obtain a base solution;

[0087] The metal salt solution and the alkaline solution are mixed to obtain inorganic particles 10 .

[0088] In some embodiments, the metal salt includes one or more of zinc salts, barium salts, nickel salts, titanium salts, tin salts, tantalum salts, zirconium salts, lithium salts, aluminum salts, manganese salts, indium salts, cadmium salts, molybdenum salts, tungsten salts, copper salts, gallium salts, and chromium salts.

[0089] In some embodiments, the metal salt includes one or more of chloride, nitrate, acetate, acetate, citrate, and lactate.

[0090] Exemplarily, the zinc salt includes one or more of zinc chloride, zinc nitrate, zinc acetate, zinc acetate, zinc citrate, and zinc lactate.

[0091] In some embodiments, in the metal salt solution, the molar concentration of the metal salt is 0.1 mol / L to 1 mol / L, for example, 0.11 mol / L to 0.19 mol / L, 0.12 mol / L to 0.18 mol / L, 0.13 mol / L to 0.17 mol / L, 0.14 mol / L to 0.16 mol / L, etc. Within the molar concentration range, it is beneficial for the metal salt to be fully dissolved and dispersed in the third solvent.

[0092] In some embodiments, the third solvent includes one or more of ethanol, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide (DMSO), acetone, acetophenone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethyl acetate, pyrrole, butyric acid, and cresol.

[0093] In some embodiments, the base includes one or more of sodium hydroxide, potassium hydroxide, tetramethylammonium hydroxide, lithium hydroxide, ammonium hydroxide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and tetrabutylammonium hydroxide.

[0094] In some embodiments, in the alkaline solution, the molar concentration of the alkali is 0.1 mol / L to 1 mol / L, for example, 0.11 mol / L to 0.19 mol / L, 0.12 mol / L to 0.18 mol / L, 0.13 mol / L to 0.17 mol / L, 0.14 mol / L to 0.16 mol / L, etc. Within the molar concentration range, it is beneficial for the alkali to be fully dissolved and dispersed in the fourth solvent.

[0095] In some embodiments, the fourth solvent includes one or more of ethanol, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide (DMSO), acetone, acetophenone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethyl acetate, pyrrole, butyric acid, and cresol.

[0096] In some embodiments, the metal salt includes metal ions, the base includes hydroxide ions, and the molar ratio of the hydroxide ions to the metal ions is (1.5-3):1, for example, (1.6-2.9):1, (1.7-2.8):1, (1.8-2.6):1, (2-2.5):1, (2.2-2.4):1, etc. Within the molar ratio range, it is beneficial for the metal salt and the base to fully react to form the inorganic particles 10.

[0097] In some embodiments, after the metal salt solution and the alkaline solution are mixed, stirring is further performed to obtain the inorganic particles 10 .

[0098] Furthermore, in some embodiments, the stirring time is 1 h to 4 h, for example, 1.2 h to 3.8 h, 1.5 h to 3.7 h, 2 h to 3.6 h, 2.5 h to 3.5 h, 2.8 h to 3 h, etc. Within the stirring time range, the metal salt solution and the alkali solution are fully mixed, which promotes the reaction between the metal salt and the alkali.

[0099] In some embodiments, after the metal salt solution and the alkaline solution are mixed, a precipitant is added to precipitate the inorganic particles 10 .

[0100] Further, in some embodiments, the precipitant includes one or more of acetone, ethyl acetate, hexane, and heptane.

[0101] In some embodiments, the molar ratio of the inorganic particles 10 to the precipitant is 1:(3-5), for example, 1:(3.2-4.8), 1:(3.5-4.6), 1:(3.6-4.5), 1:(3.8-4.2), 1:(3.6-4), etc. Within the mass ratio range, it is beneficial to fully remove the unreacted alkaline solution and the second solvent to obtain the inorganic particles 10.

[0102] In some embodiments, after adding the precipitant, centrifugation and drying are further included to remove the precipitant.

[0103] In some embodiments, the inorganic particles 10 include inorganic particles and linking group precursors connected to the surfaces of the inorganic particles, wherein the linking group precursors include one or more of hydroxyl, carboxyl, amide, amino, and aldehyde groups. It is understood that after the inorganic particles and the siloxane react, the linking group precursors are converted into linking groups, such as -COO-, -O-, -NH-CO-, -NH-, -CO-, etc.

[0104] The material of the inorganic particles is the same as the material of the inorganic particles 10 , which is described above and will not be repeated here.

[0105] The S12:

[0106] In some embodiments, the molar ratio of the inorganic particles 10 to the siloxane compound 20 is 1:(0.01-0.5), for example, 1:(0.05-0.45), 1:(0.1-0.4), 1:(0.15-0.35), 1:(0.2-0.3), 1:(0.22-0.25), etc. Within the molar ratio range, it is beneficial for the siloxane and the inorganic particles 10 to be fully combined.

[0107] In some embodiments, after the siloxane compound 20 is mixed with the inorganic particle 10 dispersion, a first ultrasonic treatment is further performed.

[0108] Further, the frequency of the first ultrasound is 20kHz to 80kHz, for example, 25kHz to 75kHz, 30kHz to 70kHz, 35kHz to 65kHz, 40kHz to 60kHz, 45kHz to 50kHz, etc. The time of the first ultrasound is 10min to 4h, for example, 0.5h to 3.8h, 0.8h to 3.5h, 1h to 3.2h, 1.5h to 3h, 2h to 2.5h, etc. In this way, it is beneficial for the siloxane compound 20 to combine with the groups on the surface of the inorganic particles 10 to achieve the modification of the inorganic particles 10.

[0109] In some embodiments, after the first ultrasound, a first resting period is also included.

[0110] Furthermore, the first standing time is 0.5h to 6h, for example, 0.6h to 5h, 0.8h to 4h, 1h to 3.5h, 1.5h to 3h, 2h to 2.5h, etc.

[0111] In some embodiments, after the siloxane compound 20 is mixed with the inorganic particle 10 dispersion, the first solvent is separated and removed to obtain an intermediate, and the intermediate is mixed with a second solvent to obtain an intermediate solution.

[0112] In some embodiments, the intermediate includes the inorganic particles 10 and the siloxane compound 20 connected to the inorganic particles 10 .

[0113] Furthermore, the intermediate includes the inorganic particles 10 and a siloxane layer coated on the surface of the inorganic particles 10 , and the material of the siloxane layer includes a siloxane compound 20 .

[0114] In some embodiments, the second solvent includes one or more of ethanol, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide (DMSO), acetone, acetophenone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethyl acetate, pyrrole, butyric acid, and cresol.

[0115] In some embodiments, in the intermediate solution, the molar concentration of the intermediate is 0.5 mmol / L to 1 mmol / L, for example, 0.55 mmol / L to 0.95 mmol / L, 0.6 mmol / L to 0.9 mmol / L, 0.65 mmol / L to 0.85 mmol / L, 0.7 mmol / L to 0.8 mmol / L, 0.72 mmol / L to 0.75 mmol / L, etc. Within the molar concentration range, it is beneficial to uniformly disperse the intermediate and promote the reaction with the fluorine-containing compound 30.

[0116] It can be understood that the siloxane compound 20 contains a silicon-oxygen bond, ie, a Si—O bond.

[0117] In some embodiments, the silicon-oxygen bond of the siloxane compound 20 reacts and connects with the connecting group of the inorganic particle 10. It can be understood that the connecting group contains -H, the silicon-oxygen bond contains -O, and -H reacts and combines with -O to generate H 2 O, so that the siloxane compound 20 is connected to the inorganic particles 10. The modification of the siloxane compound 20 is achieved.

[0118] The siloxane compound 20 is described above and will not be described in detail here.

[0119] The S13:

[0120] In some embodiments, the molar ratio of the inorganic particles 10 to the fluorine-containing compound 30 is 1:(0.01-0.5), for example, 1:(0.05-0.45), 1:(0.1-0.4), 1:(0.15-0.35), 1:(0.2-0.3), 1:(0.22-0.25), etc. Within the molar ratio range, it is beneficial for the fluorine-containing compound 30 and the intermediate to be fully combined.

[0121] In some embodiments, after the fluorine-containing compound 30 is mixed with the intermediate solution, a second ultrasonic treatment is further performed.

[0122] Further, the frequency of the second ultrasound is 20kHz to 80kHz, for example, 25kHz to 75kHz, 30kHz to 70kHz, 35kHz to 65kHz, 40kHz to 60kHz, 45kHz to 50kHz, etc. The time of the second ultrasound is 10min to 4h, for example, 0.5h to 3.8h, 0.8h to 3.5h, 1h to 3.2h, 1.5h to 3h, 2h to 2.5h, etc. In this way, it is beneficial for the fluorine-containing compound 30 to combine with the siloxane compound 20, and to achieve the modification of the inorganic particles 10 as an outer layer ligand.

[0123] In some embodiments, after the second ultrasound, a second resting step is also included.

[0124] Furthermore, the second standing time is 0.5h to 6h, for example, 0.6h to 5h, 0.8h to 4h, 1h to 3.5h, 1.5h to 3h, 2h to 2.5h, etc.

[0125] In some embodiments, after the fluorine-containing compound 30 is mixed with the intermediate dispersion, the second solvent is separated and removed to obtain a composite material.

[0126] In some embodiments, the siloxane compound 20 contains -NH 2 、-OCH 3 One or more of the .

[0127] In some embodiments, the fluorine-containing compound 30 contains -COCl.

[0128] In some embodiments, the -NH 2 and / or -OCH 3 Connect with -COCl of the fluorine-containing compound 30 to achieve modification of the fluorine-containing compound.

[0129] In some embodiments, the composite material includes inorganic particles 10 , a siloxane compound 20 connected to the inorganic particles 10 , and a fluorine-containing compound 30 connected to a surface of the siloxane compound 20 away from the inorganic particles 10 .

[0130] Furthermore, the composite material includes inorganic particles 10, a siloxane layer coated on the surface of the inorganic particles 10, and a fluorine-containing compound 30 connected to the surface of the siloxane layer away from the inorganic particles 10, the material of the siloxane layer includes siloxane, and the fluorine-containing compound 30 contains a fluorinated chain hydrocarbon group.

[0131] It can be understood that the composite material can be a structure in which the siloxane compound 20 covers the inorganic particles 10 , and the fluorine-containing compound 30 covers the siloxane.

[0132] The fluorine-containing compound 30 is described above and will not be described again here.

[0133] See also Figure 3 The embodiment of the present application also provides a light-emitting device, which includes: a first electrode 100, a first carrier functional layer 200, a light-emitting layer 300 and a second electrode 500 stacked in sequence, wherein the material of the first carrier functional layer 200 includes the composite material described above.

[0134] When the composite material is applied to the carrier functional layer in a light-emitting device, the carrier mobility can be improved, and by inhibiting the redox reaction between the carrier and the electrode interface, the efficiency and stability of the light-emitting device can be improved, thereby improving the luminescence performance and service life of the light-emitting device.

[0135] In some embodiments, the materials of the first electrode 100 and the second electrode 500 independently include one or more of metal, carbon material and metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, and the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO 2 / Ag / TiO 2 and TiO 2 / Al / TiO 2 One or more of the above. Wherein, “ / ” indicates a stacked structure, for example, AZO / Ag / AZO indicates a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence.

[0136] In some embodiments, the thickness of the first electrode 100 is 30 nm to 80 nm, for example, 42 nm to 78 nm, 45 nm to 75 nm, 48 nm to 70 nm, 50 nm to 65 nm, 55 nm to 60 nm, etc.

[0137] In some embodiments, the thickness of the second electrode 500 is 30 nm to 80 nm, for example, 42 nm to 78 nm, 45 nm to 75 nm, 48 nm to 70 nm, 50 nm to 65 nm, 55 nm to 60 nm, etc.

[0138] In some embodiments, see Figure 4 The first carrier functional layer 200 is an electron functional layer or a hole functional layer. The electron functional layer includes one or more of an electron injection layer 201 and an electron transport layer 202, and the hole functional layer includes one or more of a hole injection layer 402 and a hole transport layer 401.

[0139] In some embodiments, the thickness of the first carrier functional layer 200 is 20 nm to 60 nm, for example, 22 nm to 58 nm, 25 nm to 55 nm, 30 nm to 50 nm, 35 nm to 45 nm, 40 nm to 42 nm, etc.

[0140] In some embodiments, the material of the light-emitting layer 300 includes one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0141] The organic light-emitting material includes CBP:Ir(mppy) 3 (4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)]), TCTX:Ir(mmpy)(4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium]), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing BN covalent bonds, HLCT (hybridized localized charge transfer excited state) materials, Exciplex (exciplex) luminescent materials, one or more thereof.

[0142] The quantum dot luminescent material includes one or more of single structure quantum dots, core-shell structure quantum dots and perovskite type semiconductor materials.

[0143] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots can be respectively selected from but not limited to one or more of the group II-VI compounds, group IV-VI compounds, group III-V compounds and group I-III-VI compounds. The II-VI group compounds include one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds include one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compounds include one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb. The I-III-VI group compounds include CuInS 2 、CuInSe 2 AgInS 2 One or more of the .

[0144] As an example, the core-shell structured quantum dots include one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0145] The perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX 3 , where A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX 3 , wherein B is an organic amine cation selected from CH 3 (CH 2 ) n-2 NH 3 + or [NH 3 (CH 2 ) n NH 3 ] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2 + 、Eu 2+One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of the .

[0146] In some embodiments, the thickness of the light emitting layer 300 is 20 nm to 60 nm, for example, 22 nm to 58 nm, 25 nm to 55 nm, 30 nm to 50 nm, 35 nm to 45 nm, 40 nm to 42 nm, etc.

[0147] In some embodiments, the light emitting device further includes a second carrier functional layer 400 , and the second carrier functional layer 400 is disposed between the light emitting layer 300 and the second electrode 500 .

[0148] The second carrier functional layer 400 can be an electron functional layer or a hole functional layer. It can be understood that when the first carrier functional layer 200 is an electron functional layer, the second carrier functional layer 400 is a hole functional layer. When the first carrier functional layer 200 is a hole functional layer, the second carrier functional layer 400 is an electron functional layer.

[0149] In some embodiments, when the first carrier functional layer 200 is an electronic functional layer, the inorganic particles in the first carrier functional layer 200 include one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials, and IB-IIIA-VIA semiconductor materials, and the material of the first undoped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following, the metal oxide in the first doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 、Al 2 O 3The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor materials include one or more of InP and GaP. The IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS.

[0150] In other embodiments, when the first carrier functional layer 200 is a hole functional layer, the inorganic particles in the first carrier functional layer 200 include one or more of second doped metal oxide particles, second non-doped metal oxide particles, metal sulfide, metal selenide and metal nitride, and the metal oxide in the second doped metal oxide particles and the metal oxide in the second non-doped metal oxide particles each independently include MoO 3 , WO 3 、NiO、CrO 3 , CuO, Cu 2 O.V 2 O 5 The doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, and V, and the metal sulfide includes CuS, MoS 3 , WS 3 One or more of the metal selenides, wherein the metal selenides include MoSe 3 ,WSe 3 One or more of the above, wherein the metal nitride comprises P-type gallium nitride.

[0151] In some embodiments, when the second carrier functional layer 400 is an electronic functional layer, the material of the second carrier functional layer 400 includes one or more of the above composite material, first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials, and IB-IIIA-VIA semiconductor materials, and the material of the first undoped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 One or more of the following, the metal oxide in the first doped metal oxide particles includes ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O5 、Al 2 O 3 The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor materials include one or more of InP and GaP. The IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS.

[0152] In some other embodiments, when the second carrier functional layer 400 is a hole functional layer, the material of the second carrier functional layer 400 includes the above composite material, 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, -bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexazolyl heterotriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly[2-methoxy- 5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS doped with s-MoO 3The invention relates to one or more of derivatives of poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfide, metal selenide and metal nitride, wherein the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles each independently include MoO 3 , WO 3 、NiO、CrO 3 , CuO, Cu 2 O.V 2 O 5 The doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, and V, and the metal sulfide includes CuS, MoS 3 , WS 3 One or more of the metal selenides, wherein the metal selenides include MoSe 3 ,WSe 3 One or more of the above, wherein the metal nitride comprises P-type gallium nitride.

[0153] In some embodiments, the thickness of the second carrier functional layer 400 is 20 nm to 60 nm, for example, 22 nm to 58 nm, 25 nm to 55 nm, 30 nm to 50 nm, 35 nm to 45 nm, 40 nm to 42 nm, etc.

[0154] In some embodiments, the preparation method of the first carrier functional layer 200 and the second carrier functional layer 400 can adopt conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical coating and solution method, among which the physical coating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip-pull method, immersion method, spray coating, roll coating, casting, slit coating, and strip coating, etc.

[0155] In a fourth aspect, an embodiment of the present application further provides a display device, which includes the above-mentioned light-emitting device.

[0156] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0157] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0158] Example 1

[0159] This embodiment provides a composite material and a preparation method thereof, and the preparation method thereof is as follows:

[0160] Dissolve zinc chloride in DMF to obtain a metal salt solution with a concentration of 0.5 mol / L, dissolve sodium hydroxide in DMF to obtain an alkaline solution with a concentration of 0.6 mol / L, mix 10 mL of the metal salt solution with 20 mL of the alkaline solution, stir for 1.5 hours to obtain a clear transparent solution, add acetone to precipitate zinc oxide, centrifuge and vacuum dry to obtain zinc oxide inorganic particles, and dissolve the zinc oxide nanoparticles in ethanol to obtain a zinc oxide dispersion;

[0161] According to the ratio of zinc oxide to 3-aminopropyltrimethoxysilane = 1:0.2, 3-aminopropyltrimethoxysilane was added to the zinc oxide dispersion, ultrasonically dispersed at room temperature for 2 hours, and then allowed to stand for 2 hours, and centrifuged to remove unreacted impurities to obtain an intermediate of 3-aminopropyltrimethoxysilane-coated zinc oxide, and the intermediate was dissolved in ethanol to obtain an intermediate solution;

[0162] Perfluoroisopropionyl chloride was added to the intermediate solution in a ratio of zinc oxide to perfluoroisopropionyl chloride = 1:0.2, and ultrasonic dispersion was performed at room temperature for 2 hours. The mixture was allowed to stand for 2 hours, and unreacted impurities were removed by centrifugal filtration to obtain a composite material of 3-aminopropyltrimethoxysilane-coated zinc oxide and perfluoroisopropionyl chloride-coated 3-aminopropyltrimethoxy.

[0163] Example 2

[0164] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, perfluoroisopropanoyl chloride is replaced by perfluoroacryloyl chloride.

[0165] Example 3

[0166] This embodiment is substantially the same as Embodiment 1, except that the molar ratio of raw materials in this embodiment is replaced with zinc oxide: 3-aminopropyltrimethoxysilane: perfluoroisopropionyl chloride = 1:0.01:0.01.

[0167] Example 4

[0168] This embodiment is substantially the same as Embodiment 1, except that the molar ratio of raw materials in this embodiment is replaced with zinc oxide: 3-aminopropyltrimethoxysilane: perfluoroisopropionyl chloride = 1:0.5:0.5.

[0169] Example 5

[0170] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, perfluoroisopropionyl chloride is added to the intermediate solution and ultrasonically dispersed at room temperature for 10 minutes.

[0171] Example 6

[0172] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, perfluoroisopropionyl chloride is added to the intermediate solution and ultrasonically dispersed at room temperature for 4 hours.

[0173] Example 7

[0174] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, 3-aminopropyltrimethoxysilane is replaced by 3-methoxypropyltrimethoxysilane.

[0175] Example 8

[0176] This embodiment is basically the same as Embodiment 1, except that magnesium acetate is further added in this embodiment, and the obtained inorganic particles are magnesium-doped zinc oxide.

[0177] Example 9

[0178] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, zinc chloride is replaced by nickel acetate, and the inorganic particles are nickel oxide.

[0179] Comparative Example 1

[0180] This comparative example is substantially the same as Example 1, except that in this comparative example, perfluoroisopropanoyl chloride is replaced by pentafluorobenzoyl chloride.

[0181] Comparative Example 2

[0182] This comparative example provides a composite material, and the composite material is the zinc oxide nanoparticles prepared in Example 1.

[0183] Comparative Example 3

[0184] This comparative example provides a composite material, which is the magnesium-doped zinc oxide nanoparticles prepared in Example 8.

[0185] Comparative Example 4

[0186] This comparative example provides a composite material, and the composite material is the nickel oxide nanoparticles prepared in Example 9.

[0187] On the first day (1d) and the tenth day (10d), the hydrated particle size (DLS) of the composite materials of Examples 1 to 9 and Comparative Examples 1 to 4 was measured by dynamic light scattering (DLS), and the hydrated particle size growth rate was calculated. The results are shown in Table 1.

[0188] Table 1

[0189]

[0190] From Table 1, we can see that:

[0191] It can be seen from Examples 1 to 2 and Comparative Example 1 that after being placed for 10 days, the particle size growth rate of the composite material using perfluoroisopropanoyl chloride or perfluoroacryloyl chloride is much smaller than the particle size growth rate of pentafluorobenzoyl chloride in Comparative Example 1, indicating that the composite materials of Examples 1 to 2 are more stable and not easy to agglomerate;

[0192] From Example 1, Examples 3 to 6 and Comparative Example 2, it can be seen that the particle size of the zinc oxide inorganic particles in Comparative Example 2 increased significantly after being placed for 10 days, and obvious agglomeration occurred, which would seriously affect the performance of the composite material; while the particle size growth rate of the composite materials of Example 1 and Examples 3 to 6 was less than 10% after being placed for 10 days, indicating that the particle size growth of the composite material can be effectively avoided by controlling the amount of fluorinated chain hydrocarbon group and the reaction time;

[0193] It can be seen from Example 1, Examples 7 to 8 and Comparative Examples 2 to 3 that replacing siloxane or doping zinc oxide inorganic particles with magnesium has no significant effect on the particle size of the composite material, and the particle size growth rate is lower than that of the composite material in Comparative Examples 2 to 3 that is not modified with siloxane and fluorinated chain hydrocarbon ligands;

[0194] It can be seen from Example 9 and Comparative Example 4 that when the inorganic particles are nickel oxide, after the siloxane and fluorinated chain hydrocarbon groups are modified by this scheme, the particle size growth rate decreases significantly, indicating that it has better stability and can still exert beneficial properties under long-term storage.

[0195] Device Example 1

[0196] This embodiment also provides a light emitting device, and the preparation method thereof is as follows:

[0197] The patterned ITO substrate was ultrasonically cleaned in sequence using acetone, washing liquid, deionized water and isopropanol, each ultrasonic cleaning lasting 15 minutes, the cleaned ITO substrate was dried, and the surface of the ITO substrate was treated with ultraviolet-ozone for 5 minutes to form an anode with a thickness of 30 nm;

[0198] Depositing PEDOT:PSS on the anode, heating at 150°C for 30 min to remove moisture, and forming a hole injection layer with a thickness of 30 nm;

[0199] The ITO substrate coated with the hole injection layer was placed in a nitrogen atmosphere, TFB was deposited, and the solvent was removed by heating at 150°C for 30 min to form a hole transport layer with a thickness of 30 nm;

[0200] Depositing CdSe / ZnS quantum dot material on the hole transport layer, heating at 100° C. for 10 min to remove the solvent, and forming a quantum dot light-emitting layer with a thickness of 30 nm;

[0201] The composite material of Example 1 is dissolved in ethanol to obtain a composite material dispersion liquid, the composite material dispersion liquid is deposited on the quantum dot light-emitting layer, and annealed at 80° C. for 30 min to form an electronic functional layer with a thickness of 30 nm;

[0202] Vapor depositing 80 nm of Ag on the electronic functional layer to form a cathode;

[0203] The basic device was treated with ultraviolet curing adhesive for 3 minutes for packaging to obtain a light-emitting device.

[0204] Device Examples 2 to 8

[0205] Device Examples 2 to 8 are substantially the same as Device Example 1, except that Device Examples 2 to 8 use the composite materials of Examples 2 to 8 to replace the composite materials of Example 1, respectively.

[0206] Device Example 9

[0207] Device Example 9 is substantially the same as Device Example 1, except that in Device Example 9, the hole injection layer and the hole transport layer are replaced by a hole functional layer, and the preparation method of the hole functional layer is as follows:

[0208] The dispersion of the composite material prepared in Example 9 was deposited on the anode and heated at 150° C. for 30 min to remove the solvent, thereby forming a hole functional layer with a thickness of 30 nm.

[0209] Device Example 10

[0210] This device embodiment is basically the same as device embodiment 9, except that the preparation method of the electronic functional layer in this device embodiment is as follows:

[0211] The ZnO solution was spin-coated on the light-emitting layer at a speed of 3400 r / min for 40 s. After the spin coating, the layer was annealed in a nitrogen atmosphere at a temperature of 100° C. for 15 min to obtain a 30 nm electronic functional layer.

[0212] Device Comparison Examples 1 to 3

[0213] Device comparative examples 1 to 3 are substantially the same as device embodiment 1, except that the device comparative examples use the materials of comparative examples 1 to 3 to replace the composite material of embodiment 1.

[0214] Device Comparison Example 4

[0215] Device comparative example 4 is substantially the same as device embodiment 10, except that the device comparative example uses the material of comparative example 4 to replace the composite material of embodiment 9.

[0216] On the first day (1d) and the tenth day (10d), the external quantum efficiency EQE of the light-emitting devices of device embodiments 1 to 10 and comparative examples 1 to 4 was tested to obtain the external quantum efficiency EQE of the light-emitting devices on the first day and the tenth day, and the decrease rate of EQE was calculated. The results are shown in Table 2.

[0217] Among them, the external quantum efficiency EQE test method is: measured by LabView controlling the efficiency test system built by QE PRO spectrometer, Keithley2400, and Keithley 6485, with a driving current of 2mA.

[0218] Table 2

[0219]

[0220]

[0221] From Table 2, we can see that:

[0222] It can be seen from device embodiments 1 to 2 and device comparative example 1 that the light-emitting device prepared using the composite material of perfluoroisopropanoyl chloride or perfluoroacryloyl chloride has a luminous efficiency much higher than the light-emitting device prepared using pentafluorobenzoyl chloride in comparative example 1, whether it is 1d or 10d, and the luminous efficiency decrease rate of the light-emitting device of device embodiments 1 to 2 is also significantly lower than that of the light-emitting device of device comparative example 1, indicating that the light-emitting device of device embodiments 1 to 2 has a higher luminous efficiency and is more stable;

[0223] It can be seen from device example 1, device examples 3 to 6 and device comparative example 2 that the luminous efficiency of the light-emitting device of device comparative example 2 significantly decreases after being placed for 10 days; while the luminous efficiency of the light-emitting devices of device example 1 and device examples 3 to 6 is always maintained at more than 8%, and the luminous efficiency decrease rate is also at a level below 20%, indicating that the luminous efficiency of the light-emitting devices is not prone to loss;

[0224] It can be seen from device example 1, device examples 7 to 8 and device comparative examples 2 to 3 that replacing siloxane or doping zinc oxide inorganic particles with magnesium has no significant effect on the luminous efficiency of the light-emitting device. Whether it is 1d or 10d, its luminous efficiency is significantly higher than that of the light-emitting device prepared by the composite material not modified with siloxane and fluorinated chain hydrocarbon ligand in device comparative examples 2 to 3;

[0225] It can be seen from device embodiments 9 to 10 and comparative examples 2 and 4 that whether the material of the electronic functional layer or the hole functional layer is prepared by adopting this solution, the luminous efficiency of the light-emitting device can be effectively improved.

[0226] The composite materials and preparation methods thereof, light-emitting devices, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: include: Inorganic particles, siloxane compounds and fluorine-containing compounds; wherein the siloxane compound connects the inorganic particles and the fluorine-containing compound, and the fluorine-containing compound contains a fluorinated chain hydrocarbon group.

2. The composite material according to claim 1, characterized in that In the composite material, the molar ratio of the inorganic particles, the siloxane compound and the fluorine-containing compound is 1:(0.005-0.45):(0.005-0.4).

3. The composite material according to claim 1, characterized in that The inorganic particles and the siloxane compound are connected via a connecting group; and / or The siloxane compound comprises alkoxysiloxane; and / or The fluorinated hydrocarbon group is a straight-chain or branched fluorinated alkyl group having 1 to 10 carbon atoms in the main chain, a straight-chain or branched fluorinated alkenyl group having 1 to 10 carbon atoms in the main chain, or a combination of these groups.

4. The composite material according to claim 3, characterized in that The material of the inorganic particles includes one or more of a first doped metal oxide particle, a first undoped metal oxide particle, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material and an IB-IIIA-VIA semiconductor material. The material of the first undoped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2 and Ta2O5. The metal oxide in the first doped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5 and Al2O3. The doping element in the first doped metal oxide particle includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In and Ga. The IIB-VIA semiconductor material includes one or more of ZnS, ZnSe and CdS. The IIIA-VA semiconductor material The material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; one or more of second doped metal oxide particles, second undoped metal oxide particles, metal sulfides, metal selenides and metal nitrides, the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, Cu2O, V2O5, the doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, and the metal nitride includes P-type gallium nitride; and / or The average particle size of the inorganic particles is 5nm to 10nm; and / or The linking group includes one or more of -COO-, -O-, -NH-CO-, -NH-, -CO-; and / or The alkoxysiloxane includes one or more of (3-mercaptopropyl)trimethoxysilane, 3-aminopropyltrimethoxysilane, (3-propylamino)propyltriethoxysilane, and 3-methoxypropyltrimethoxysilane; and / or The fluorine-containing compound includes one or more of perfluoroisopropionyl chloride, perfluoro-n-butyryl chloride, perfluoroacryloyl chloride and perfluorohexanoyl chloride.

5. The composite material according to claim 3, characterized in that The silicon-oxygen bond of the siloxane compound is connected to the connecting group; and / or The siloxane compound contains one or more of -NH- and -OCH2-, the fluorine-containing compound contains -CO-, and the -NH- and / or -OCH2- in the siloxane compound are connected to the -CO- of the fluorine-containing compound.

6. A method for preparing a composite material, characterized in that: include: Providing an inorganic particle dispersion, wherein the inorganic particle dispersion comprises inorganic particles and a first solvent; Providing a siloxane compound, and mixing the siloxane compound with the inorganic particle dispersion to obtain an intermediate solution, wherein the intermediate solution includes an intermediate and a second solvent; A fluorine-containing compound is provided, wherein the fluorine-containing compound contains a fluorinated chain hydrocarbon group, and the fluorine-containing compound is mixed with the intermediate solution to obtain a composite material.

7. The method for preparing a composite material according to claim 6, characterized in that: The inorganic particles and the siloxane compound are connected via a linking group, wherein the linking group includes one or more of -COO-, -O-, -NH-CO-, -NH-, and -CO-; and / or The siloxane compound includes one or more of (3-mercaptopropyl)trimethoxysilane, 3-aminopropyltrimethoxysilane, (3-propylamino)propyltriethoxysilane, and 3-methoxypropyltrimethoxysilane; and / or The fluorine-containing compound includes one or more of perfluoroisopropionyl chloride, perfluoro-n-butyryl chloride, perfluoroacryloyl chloride, and perfluorohexanoyl chloride; and / or The first solvent and the second solvent independently include one or more of ethanol, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethanol, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, ethyl acetate, pyrrole, butyric acid, and cresol.

8. The method for preparing a composite material according to claim 6, characterized in that: The molar ratio of the inorganic particles, the siloxane compound and the fluorine-containing compound is 1:(0.01-0.5):(0.01-0.5); and / or In the inorganic particle dispersion, the molar concentration of the inorganic particles is 0.3 mmol / L to 0.8 mmol / L; and / or In the intermediate solution, the molar concentration of the intermediate is 0.5 mmol / L to 1 mmol / L.

9. The method for preparing a composite material according to claim 6, characterized in that: The intermediate includes the inorganic particles and a siloxane compound connected to the inorganic particles; and / or The composite material includes inorganic particles, a siloxane compound connected to the inorganic particles, and a fluorine-containing compound connected to a side of the siloxane compound away from the inorganic particles.

10. A light emitting device, characterized in that: include: A first electrode, a first carrier functional layer, a light-emitting layer and a second electrode are sequentially stacked, wherein the material of the first carrier functional layer comprises the composite material according to any one of claims 1 to 5.

11. The light emitting device according to claim 10, characterized in that: The light-emitting device also includes a second carrier functional layer, which is arranged between the light-emitting layer and the second electrode; the first carrier functional layer is an electron functional layer, and the second carrier functional layer is a hole functional layer, or the first carrier functional layer is a hole functional layer, and the second carrier functional layer is an electron functional layer.

12. The light emitting device according to claim 11, characterized in that: The materials of the first electrode and the second electrode respectively include one or more of metal, carbon material and metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The material of the light-emitting layer includes 4,4'-bis(N-carbazole)-1,1'-biphenyl: tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine: tris[2-(p-tolyl)pyridine iridium], diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonds, HLCT materials, Exciplex luminescent materials, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSe S, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs , GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, G aInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, CuInS2, CuInSe2, AgInS2, CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZ One or more of nSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, InP / ZnSe / ZnS, AMX3 and BMX3, where A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of; B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n ≥ 2; and / or When the first carrier functional layer is an electronic functional layer, the inorganic particles in the first carrier functional layer include one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials, the material of the first undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, the metal oxide in the first doped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, Al2O3, the doping element in the first doped metal oxide particles includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, the IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, CdS, the IIIA-VA semiconductor materials include I nP, GaP, the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; when the first carrier functional layer is a hole functional layer, the inorganic particles in the first carrier functional layer include one or more of second doped metal oxide particles, second non-doped metal oxide particles, metal sulfides, metal selenides and metal nitrides, the metal oxide in the second doped metal oxide particles and the metal oxide in the second non-doped metal oxide particles each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, Cu2O, V2O5, the doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, and the metal nitride includes P-type gallium nitride; and / or When the second carrier functional layer is an electronic functional layer, the material of the second carrier functional layer includes one or more of the composite material according to any one of claims 1 to 5, first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials, the material of the first undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5, the metal oxide in the first doped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3, and the first doped The doping elements in the heterogeneous metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS, the IIIA-VA semiconductor material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; or, when the second carrier functional layer is a hole functional layer, the material of the second carrier functional layer includes the composite material according to any one of claims 1 to 5, 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri (N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylenevinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfides, metal selenides and One or more of the metal nitrides, the metal oxide in the second doped metal oxide particles and the metal oxide in the second non-doped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, Cu2O, V2O5, the doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, and the metal nitride includes P-type gallium nitride. , 13. The light emitting device according to claim 11, characterized in that: The thickness of the first electrode is 30 nm to 80 nm; and / or The thickness of the first carrier functional layer is 20nm to 60nm; and / or The thickness of the light-emitting layer is 20nm to 60nm; and / or The thickness of the second carrier functional layer is 20nm to 60nm; and / or The thickness of the second electrode is 30 nm to 80 nm.

14. A display device, characterized in that: The display device comprises the light emitting device according to any one of claims 10 to 13.